Preparation and morphology analysis of nano-sized iron oxide - SUN Tian-hao; HAO Su-ju; JIANG Wu-feng; ZHANG Yu-zhu (Fenmo yejin jishu)
The nano-sized iron oxide (Fe2O3 nano-rods) was prepared by hydrothermal method with Fe(NO3)3·9H2O as the iron source, using anhydrous ethanol and ethylenediamine as the surfactant. The morphology of the Fe2O3 nano-rods was observed and analyzed by scanning electron microscope, and the effects of the Fe(NO3)3·9H2O mass fraction and the reaction temperature on the particle size of Fe2O3 nano-rods were studied. The results show that, the length and width of the Fe2O3 nano-rods are about 500～600 nm and 50～60 nm, respectively. The effect of temperature on the Fe2O3 nano-rod morphology is not significant at 160～220 ℃. The increase of iron source mass fraction in a certain range decreases the particle size of Fe2O3 nano-rods. The formation mechanism of the Fe2O3 nano-rods is as follows: the iron source reacts in the strongly alkaline solution to form the brown-yellow flocculent precipitated α-FeOOH, which is dehydrated to form the Fe2O3 nano-rods under the influence of ethylenediamine in a high temperature and high pressure environment.